A study on the importance of cross-class interactions of younger children with older students in co-ed schools in India - Datta, Ashim (Journal of Language, Literature, Social and Cultural Studies, 2023)
The importance of factors in the educational environment is very important to build up a future career. Especially among children environmental interaction makes them learn behaviour of the society. The aim of the study is to show the benefits of cross-class interactions and co-ed education among children in Indian schools. A detailed and critical analysis of the factors responsible for the development of children's education is represented. This includes the reflection of cross-class interactions and co-ed education among the children. It also relates to theory for its practical implementation and gets the best outcome. The presentation of the factors responsible for cross-class interactions and co-ed education among children in Indian schools is collected from the primary source. This consists of a survey among 70 responders of the society. The collection of the information is represented and analyzed through the statistical analyzing tool SPSS. The extracted data by the statistical tool makes the presentation a major amount of responders' opinions based on the relativity of this analysis. It shows all the benefits of the factors implemented for cross-class interactions and co-ed education among the children in Indian schools.